2022
DOI: 10.3390/v14020402
|View full text |Cite
|
Sign up to set email alerts
|

Ergosterol Peroxide Inhibits Porcine Epidemic Diarrhea Virus Infection in Vero Cells by Suppressing ROS Generation and p53 Activation

Abstract: Porcine epidemic diarrhea virus (PEDV) is an alphacoronavirus that causes severe watery diarrhea in piglets with high morbidity and mortality, resulting in serious economic losses to the farming industry. Ergosterol peroxide (EP) is a sterol with diverse biological activities including antiviral activity. In this study, we explored whether EP extracted from the fruiting body of the mushroom Cryptoporus volvatus had the potential to inhibit PEDV infection in Vero cells. The results revealed that EP had a remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…It was reported that a boiled extract of wogonin enables the interception of viral activity ( Li-Weber, 2009 ). Wogonin might interpose the virus–cell membrane fusion of PEDV through spike protein (S), inhibiting viral internalization ( Liu et al., 2022 ). Additionally, the effect on PEDV release may also be mediated by the modulation of innate immune responses ( Ma et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that a boiled extract of wogonin enables the interception of viral activity ( Li-Weber, 2009 ). Wogonin might interpose the virus–cell membrane fusion of PEDV through spike protein (S), inhibiting viral internalization ( Liu et al., 2022 ). Additionally, the effect on PEDV release may also be mediated by the modulation of innate immune responses ( Ma et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…To examine the effect of wogonin on PEDV inactivation, PEDV (MOI = 0.05) and wogonin (50 μM) were incubated together at 37°C for 2 h. Then, the mixture was washed with PBS and ultracentrifuged at 90,000 × g for 1.5 h at 4°C in 20% sucrose buffer (w/w) to purify the virions. Subsequently, the virions were resuspended in the culture medium, and the cell lysates were harvested for RT-qPCR ( Liu et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PEDV triggers caspase-independent apoptosis through the activation of the mitochondrial apoptosis-inducing factor (AIF) and induces caspase-8- and caspase-3-mediated apoptosis in the late stages of infection [ 7 , 8 ]. The reactive oxygen species (ROS)-p53 pathway participates in PEDV-induced apoptosis [ 11 ]. PDCoV causes caspase-dependent intrinsic apoptosis by triggering the release of the mitochondrial cytochrome c into the cytoplasm [ 9 ].…”
Section: Important Host Factors Involved In Pecov Replicationmentioning
confidence: 99%
“…Ergosterol peroxide restricts PEDV internalization, replication and release. In addition, it has the ability to inactivate PEDV virions and alleviate PEDV-induced apoptosis [ 11 ]. The aqueous leaf extract of the Moringa oleifera tree is able to suppress PEDV-induced oxidative stress (e.g., reduce ROS and malondialdehyde (MDA) production and restore glutathione peroxidase (GSH-Px) activity) and inhibit apoptosis.…”
Section: Bioactive Compounds With Anti-pecov Activitymentioning
confidence: 99%